Saturn - Brewer, Duncan, 1938- (New York : Marshall Cavendish, 1992)
Examines the physical characteristics and conditions of Saturn, describing its position in relation to the sun and other planets and surveying humanity's attempts to penetrate its mysteries.
At head of title: Exploring the planets.
Includes bibliographical references (p. 61) and index.
Keywords: Saturn (Planet) -- Juvenile literature; Saturn (Planet); Saturn (Planet) -- Exploration -- Juvenile literature